Comparison of Organic and Conventional Agriculture in the Czech Republic: A Systematic Review - Hana Vašková; Pavel Saska (Agriculture)
This systematic review aims to comprehensively examine publications that compared conventional and organic agriculture in the Czech Republic. Agriculture in the Czech Republic is unique because of considerable variability in natural and climatic conditions and from a historical context. The ultimate objective of this systematic review was to identify possible research gaps that could serve as a background for updating national research policy. The search for suitable publications was performed in Scopus and Web of Science, and screening for eligibility followed the PRISMA approach. In total, 65 publications satisfied the inclusion criteria, the extraction of which provided 380 data records. Crop production appeared to be the most frequent research theme (204 records), followed by economy (122 records), biodiversity (n = 30), animal production (n = 18) and food (n = 6). Unfortunately, numerous records suffer from methodological and statistical flaws. The research gaps identified in this systematic review include important crops, comparisons between varieties and individual practices, topics related to drought, biodiversity-oriented research including ecosystem services, and meat or egg production. We propose that, to obtain robust comparisons between the two farming systems across multiple areas of research, one large experiment covering several organic and conventional farms across the country is needed.